Do VIX futures contribute to the valuation of VIX options?. Issue 9 (18th October 2021) - Tong, Chen; Huang, Zhuo; Wang, Tianyi
Abstract: As the volatility index (VIX) is nontradable, most investors use the exchange‐traded VIX futures to hedge their exposures in VIX options. However, the information role of VIX futures in pricing VIX options is not fully explored empirically. This paper derives two types of VIX option pricing formula using VIX index and VIX futures as state variables accordingly based on a simple discrete‐time VIX dynamics with long memory and asymmetric jumps. Empirical results show that models utilizing VIX futures significantly outperform competing models based on S&P 500 index (SPX) returns, realized volatility, or the VIX index itself. Our findings are robust in out‐of‐sample.